On a Stream Error-Correcting Code - Markovski, Smile; Bakeva, Verica (Institute of Informatics, Faculty of Natural Sciences and Mathematics, Ss. Cyril and Methodius University in Skopje, Macedonia, 2001)
We use quasigroups to define suitable codes of stream nature. These codes are error-correcting with high probability.
Keywords: quasigroup, code, error-correcting code